Incidence and Risk Factors for Maternal Hypoxaemia During Induction of General Anesthesia for Non-elective Caesarean Section: A Prospective Multicentre Study. Issue 2 (24th June 2021) - Bonnet, M.P.; Mercier, F.J.; Vicaut, E.; Galand, A.; Keita, H.; Baillard, C
Abstract : ( British J Anaesthesia . 2020;125:e81–e87) General anesthesia, which can increase the risk of respiratory complications, is used in about 5% of deliveries and is mainly used in emergency cesarean sections. One study found that hypoxemia affected 2% of cesarean patients undergoing general anesthesia, but no risk factors were identified. This study aimed to determine the incidence and risk factors of hypoxemia in patients undergoing general anesthesia for non-elective cesarean delivery.